DETERMINANTS OF INDONESIA’S NON-OIL AND GAS EXPORT TO JAPAN - Rohani; Dicky Iranto (Econosains Jurnal Online Ekonomi dan Pendidikan, 2020)
This study aims to determine the impact of the Japanese economy affected by the economic crisis on the performance of Indonesian exports to Japan before and after the economic crisis. By using Japan's real GDP, real exchange rate, inflation, and the crisis dummy of Indonesia's non-oil and gas exports to Japan in 2003-2017. This study uses the VECM (Vector Error Correction Model) method to determine the short and long-term relationships of the research variables. The results obtained are: (1) Before the crisis, Indonesia's non-oil and gas exports to Japan showed positive results compared to after the crisis, (2) Japan's demand seen from Japan real GDP shows that there is a negative relationship to Indonesian exports to Japan after the crisis, (3) real exchange rate shows a positive relationship before the crisis and after the crisis shows a negative relationship, and (4) Inflation has a negative influence on Indonesia's non-oil and gas exports to Japan in the long run.